The Effect of Macroeconomic Factors on Equity Mutual Fund Returns on the Bibit Application, Moderated by JCI Volatility (2020-2024) - Suryani; Euis Mufahamah; Anita (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of inflation, interest rates, and exchange rates on stock mutual fund returns on the Bibit application with JCI volatility as a moderation variable. The approach used is quantitative with multiple linear regression analysis methods and Moderated Regression Analysis (MRA). The data used is secondary data that includes inflation rates, interest rates, exchange rates, JCI volatility, and stock mutual fund returns in certain research periods. The results of the study show that partially inflation, interest rates, and exchange rates have a significant influence on the return of stock mutual funds. In addition, JCI volatility has been proven to be able to moderate the relationship between inflation and exchange rates on stock mutual fund returns, but it is unable to moderate the effect of interest rates on returns. These findings indicate that macroeconomic conditions and stock market volatility dynamics play an important role in determining the performance of stock mutual funds. Therefore, investors and investment managers need to carefully consider these factors in their investment decision-making, especially in the use of digital platforms such as the Bibit application, in order to maximize potential profits and minimize risks that may arise.